Enhanced recovery of a biofilm-enabled microbial fuel cell-based biosensor from toxic shocks for wastewater quality monitoring - Tang, Nehemiah Sheng En (Nanyang Technological University, 2022)
Microbial fuel cells (MFC) are devices driven by bacterial metabolism and biofilm formation, as has been widely applied in various fields. This is due to its unique capability of sustainable power generation utilizing chemical energy stored in organic wastes. By harnessing bacteria’s ability to respire and oxidize various electron donors with diverse enzymes, MFCs are often employed in environmental pollution treatment and monitoring. However, multiple limitations to this technology still exist due to its novel nature, such as low sensitivity, short-term performance and low specificity. Hence, research is conducted to hopefully improve upon the current models of MFC-based biosensors, as the technology is shown to be quite promising in terms of providing real-time, in-situ monitoring with a compact nature and is self-powered. Extensive studies have been carried out to increase detection limits and throughput, along with expanding on trace monitoring.